2015
DOI: 10.4194/1303-2712-v15_3_07
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The survival rate and growth parameters of grayling fry were determined after stocking them in the wild. Before their release (7 July 2011) into the wild, the fry were reared for 7 weeks in the hatchery, in two groups: (i) fry fed on live daphnids and live chironomids larvae (LFG), (ii) fry fed on a pellet diet (PFG). On the 2 October 2011, the fish survival rate was checked; the fish were caught in the wild. The survival rate and specific growth rates were higher in the LFG than in the PFG. The most effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The waters of the Odra system are the crucial migratory road for salmonids that use the Drawa River (tributary to the Noteć that supplies the Warta River) for breeding [59]. Therefore, the parameters of the Odra River system directly impact the ecological status of the entire river basin.…”
Section: Ecological Disaster and Consequencesmentioning
confidence: 99%
“…The waters of the Odra system are the crucial migratory road for salmonids that use the Drawa River (tributary to the Noteć that supplies the Warta River) for breeding [59]. Therefore, the parameters of the Odra River system directly impact the ecological status of the entire river basin.…”
Section: Ecological Disaster and Consequencesmentioning
confidence: 99%
“…A series of studies on stocked salmonid fry, fed live food prior to release, have repeatedly shown that postrelease growth and survival rates are higher in individuals with live-food experience (Czerniawski et al 2010(Czerniawski et al , 2011(Czerniawski et al , 2015, but also that the type of prey used in training can influence the results (Czerniawski et al 2011). Follow-up laboratory studies suggest that effects are due to improved foraging per se (Ciszewski et al 2020).…”
Section: Social Transfermentioning
confidence: 99%